Development of acceleration factors for reliability testing of mechanical equipment. (1st January 2014) - Evans, John W.; Chen, Guangming; Evans, Jillian Y.; Bartos, James
Accelerated life tests allow for reduction of test time to demonstrate targeted life of a component for a given level of reliability. This is accomplished by increasing loads on the component or by compressing the time scale in relation to the service environment. The acceleration factor provides a quantitative estimate of the relationship between the test condition and the field condition for this purpose. This paper provides a detailed process, for developing acceleration factor models for reliability testing of mechanical components. Several examples are given for various types of mechanical components undergoing wear-out processes.